CSC669 - Cryptographic Algorithms / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics and Media (Universiti Teknologi MARA (UiTM), 2021)
Cryptography plays a key role in ensuring the privacy and integrity of data and the security of computer networks. The course will provide an overview of an introductory level of cryptography written from a modern, computer science perspective. This course will be blend of theory and practice, covering standardized cryptosystems widely used in practice without sacrificing rigor or an emphasis on foundations. The course also shed light on the entrepreneur and to prepare the students with the essence of entrepreneurship and business planning skills that is essential for the success of new ventures. The subject delivery combines both theoretical and practical aspects of cryptography algorithms